Formation of the portfolio of projects for informatization programs - Ion Bolun (Computer Science Journal of Moldova, 2009)
in informatization programs are approached: criteria of efficiency, general problem, aggregate problem in continuous form, general problem in discrete form and solving of problems. As criterion of informatization projects' economic efficiency, the total profit maximization due to investments is used. In preliminary calculations, the opportunity of considering continuous dependences of profit on the volume of investments by domain activities is grounded. Eleven classes of such dependences are investigated and analytical solutions and algorithms for solving formulated problems are described.